Lipid-induced endothelial vascular cell adhesion molecule 1 promotes nonalcoholic steatohepatitis pathogenesis - Furuta, Kunimaro; Guo, Qianqian; Pavelko, Kevin D.; Lee, Jeong-Heon; Robertson, Keith D.; Nakao, Yasuhiko; Melek, Jan; Shah, Vijay H.; Hirsova, Petra; Ibrahim, Samar H. (The Journal of clinical investigation, 2021)
Monocyte homing to the liver and adhesion to the liver sinusoidal endothelial cells (LSECs) are key elements in nonalcoholic steatohepatitis (NASH) pathogenesis. We reported previously that VCAM-1 mediates monocyte adhesion to LSECs. However, the pathogenic role of VCAM-1 in NASH is unclear. Herein, we report that VCAM-1 was a top upregulated adhesion molecule in the NASH mouse liver transcriptome. Open chromatin landscape profiling combined with genome-wide transcriptome analysis showed robust transcriptional upregulation of LSEC VCAM-1 in murine NASH. Moreover, LSEC VCAM-1 expression was significantly increased in human NASH. LSEC VCAM-1 expression was upregulated by palmitate treatment in vitro and reduced with inhibition of the mitogen-activated protein 3 kinase (MAP3K) mixed lineage kinase 3 (MLK3). Likewise, LSEC VCAM-1 expression was reduced in the Mlk3-/- mice with diet-induced NASH. Furthermore, VCAM-1 neutralizing Ab or pharmacological inhibition attenuated diet-induced NASH in mice, mainly via reducing the proinflammatory monocyte hepatic population as examined by mass cytometry by time of flight (CyTOF). Moreover, endothelium-specific Vcam1 knockout mice were also protected against NASH. In summary, lipotoxic stress enhances the expression of LSEC VCAM-1, in part, through MLK3 signaling. Inhibition of VCAM-1 was salutary in murine NASH and might serve as a potential therapeutic strategy for human NASH.